On the trail of Scandinavia’s early metallurgy: provenance, transfer and mixing - Wrobel Nørgaard, Heide; Pernicka, Ernst; Vandkilde, Helle (PLOS ONE, 2019)
The rich and long-lasting Nordic Bronze Age was dependent throughout on incoming flows of copper and tin. The crucial turning point for the development of the NBA can be pinpointed as the second phase of the Late Neolithic (LN II, c. 2000-1700 BC) precisely because the availability and use of metal increased markedly at this time. But the precise provenance of copper reaching Scandinavia in the early second millennium is still unclear and our knowledge about the driving force leading to the establishment of the Bronze Age in southern Scandinavia is fragmentary and incomplete. This study, drawing on a large data set of 210 samples representing almost 50% of all existing metal objects known from this period in Denmark, uses trace element (EDXRF) and isotope analyses (MC-ICP-MS) of copper-based artifacts in combination with substantial typological knowledge to profoundly illuminate the contact directions, networks and routes of the earliest metal supplies. It also presents the first investigation of local recycling or mixing of metals originating from different ore regions. Both continuity and change emerge clearly in the metal-trading networks of the Late Neolithic to the first Bronze Age period. Artifacts in LN II consist mainly of high-impurity copper (so-called fahlore type copper), with the clear exception of British imports. Targeted reuse of foreign artifacts in local production is demonstrated by the presence of British metal in local-style axes. The much smaller range of lead isotope ratios among locally crafted compared to imported artifacts is also likely due to mixing. In the latter half of Nordic LN II (1800-1700 BC), the first signs emerge of a new and distinct type of copper with low impurity levels, which gains enormously in importance later in NBA IA.